46th AIAA Fluid Dynamics Conference 2016
DOI: 10.2514/6.2016-3255
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Sinusoidal Leading-Edged Wings

Abstract: Observations of maneuvering humpback whales have revealed unique hydrodynamic performance hypothesized to be a result of tubercles on the leading-edge of the whales' pectoral flippers. Inspired by this biological observation, it is shown sinusoidal leading-edge wings prevent the dramatic loss of lift caused by stall and instead generate a gradual decrease of lift with as much as 25% higher lift in the poststall regmine. Six different wing geometries, smooth and sinusoidal leading-edge models, swept and unswept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In contrast, it was also found that the sinusoidal structure applied on the leading edge will partially reduce the thrust of bionic rotors LE with PA 12 and Resin 9400, respectively. This is possibly due to the disturbance of flow distribution that arose by the sinusoidal structure near the leading edge [38]. Further, a more notable drop in the thrust of bionic rotor LE-TE-S with Resin 9400 can be found, resulting from the reduction of total effective lifting area by SMD, while the bionic rotor LE-TE-A with Resin 9400 showed a significant increase thrust during the whole speed range (3000-6000 rpm).…”
Section: Thrust Generationmentioning
confidence: 92%
“…In contrast, it was also found that the sinusoidal structure applied on the leading edge will partially reduce the thrust of bionic rotors LE with PA 12 and Resin 9400, respectively. This is possibly due to the disturbance of flow distribution that arose by the sinusoidal structure near the leading edge [38]. Further, a more notable drop in the thrust of bionic rotor LE-TE-S with Resin 9400 can be found, resulting from the reduction of total effective lifting area by SMD, while the bionic rotor LE-TE-A with Resin 9400 showed a significant increase thrust during the whole speed range (3000-6000 rpm).…”
Section: Thrust Generationmentioning
confidence: 92%